Lessons from New American Schools' scale-up phase : prospects for bringing designs to multiple schools - Bodilly, Susan J.; New American Schools (Organization); Rand Corporation (Santa Monica, Calif. : RAND, 1998)
New American Schools was established in 1991 to help schools transform themselves into high-performing organizations. This report is a formative assessment of the first two years (1995-1997) of the scale-up phase, during which NAS partnered with 10 jurisdictions to implement design-based programs for improving student performance. A series of lessons emerged from this analysis: (1) The effort at school reform is complex because of the multiple actors involved. (2) Design teams do not accomplish implementation by themselves but only with the cooperation of schools and districts. (3) Teachers found stable school and district leadership and clear signals about the effort's priority to be important. Perhaps the most important lesson is that there still are no silver bullets for ensuring the implementation of reforms, but several districts have made significant progress in the two-year period.
Figures ix -- Tables xi -- Chapter 2 History of NAS and the Scale-Up Strategy 7 -- Chapter 3 Research Approach and Methods 21 -- Chapter 4 Findings on Progress Towards Implementation 35 -- Chapter 5 The Influence of the Selection Process and School Climate 43 -- Chapter 6 Influence of Design and Team Factors 59 -- Chapter 7 Influence of School Structural and Site Factors 79 -- Chapter 8 Influence of Jurisdictional and Institutional Factors 85 -- Chapter 9 Caveats and Conclusions 107 -- Appendix A Backgroound History of New American Schools 115 -- Appendix B Descriptions and Designs 119.
"MR-942-NAS"--Page 4 of cover.
Includes bibliographical references (pages 135-140).
Print version record.
English.
eBooks on EBSCOhost
Keywords: New American Schools (Organization); New American Schools (Organization); School improvement programs -- United States -- Case studies; School management and organization -- United States -- Case studies; School districts -- United States -- Case studies; School environment -- United States -- Case studies; Enseignement -- Réforme -- États-Unis -- Études de cas; Administration scolaire -- États-Unis -- Études de cas; Circonscriptions scolaires -- États-Unis -- Études de cas; Milieu scolaire -- États-Unis -- Études de cas; EDUCATION -- Administration -- General; School districts; School environment; School improvement programs; School management and organization; United States; Education; Social Sciences; Theory & Practice of Education; Case studies